Plant domestication decreases both constitutive and induced chemical defences by direct selection against defensive traits - Xoaquín Moreira (Nature Portfolio, 2018)
Abstract Studies reporting domestication effects on plant defences have focused on constitutive, but not on induced defences. However, theory predicts a trade-off between constitutive (CD) and induced defences (ID), which intrinsically links both defensive strategies and argues for their joint consideration in plant domestications studies. We measured constitutive and induced glucosinolates in wild cabbage (Brassica oleracea ssp. oleracea) and two domesticated varieties (B. oleracea var. acephala and B. oleracea var. capitata) in which the leaves have been selected to grow larger. We also estimated leaf area (proxy of leaf size) to assess size-defence trade-offs and whether domestication effects on defences are indirect via selection for larger leaves. Both CD and ID were lower in domesticated than in wild cabbage and they were negatively correlated (i.e. traded off) in all of the cabbage lines studied. Reductions in CD were similar in magnitude for leaves and stems, and CD and leaf size were uncorrelated. We conclude that domestication of cabbage has reduced levels not only constitutive defences but also their inducibility, and that reductions in CD may span organs not targeted by breeding. This reduction in defences in domesticated cabbage is presumably the result of direct selection rather than indirect effects via trade-offs between size and defences.